2016
DOI: 10.1039/c6ra08956a
|View full text |Cite
|
Sign up to set email alerts
|

Solid state fermentation of soybean waste and an up-flow column bioreactor for continuous production of camptothecine by an endophytic fungus Fusarium oxysporum

Abstract: The potential of an endophytic fungus Fusarium oxysporum (NCIM 1383) to produce the anti-cancer prodrug 'camptothecine (CPT)' by solid state fermentation (SSF) of agro-industrial by-products was investigated. Amongst the various substrates used under optimized SSF conditions, soybean meal was found to be the most efficient medium for optimum production of CPT by the fungus. The effect of the addition of different complex protein sources to the soybean meal substrate on productivity by the fungus was also studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Soybean meal is a by-product of the soybean seed industry, which is commonly used for animal feeding [1,2] or rejected directly in nature, then causing serious problems to municipalities and to the environment [3,4]. In order to reduce pollution related to soybean seed industry's by-products and wastes, numerous usages have been proposed and tested: broiler breeding [1], growing substrate or source of specific compounds for microorganisms [3,5], biosurfactants [6], and biodiesel production among others. But soybean waste and meal particularly have not been exploited for the production of polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…Soybean meal is a by-product of the soybean seed industry, which is commonly used for animal feeding [1,2] or rejected directly in nature, then causing serious problems to municipalities and to the environment [3,4]. In order to reduce pollution related to soybean seed industry's by-products and wastes, numerous usages have been proposed and tested: broiler breeding [1], growing substrate or source of specific compounds for microorganisms [3,5], biosurfactants [6], and biodiesel production among others. But soybean waste and meal particularly have not been exploited for the production of polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…In the endophytic fungi F. solani from Ferocactus latispinus, the pH value and nitrogen/carbon ratio were found to affect polyketide production and were optimized, resulting in a higher yield (476 µmol/L) [280]. In addition, a bioreactor was developed to monitor the consistent production of metabolites [281]. The colonization of plant internal tissues by fungal endophytes (dark condition) showed that light treatment decreased taxol production in Paraconiothyrium SSM001 and decreased the level of gene expression [282].…”
Section: Optimization Of Culture Conditionsmentioning
confidence: 99%
“…Pulp and paper solid waste were pre-treated with acid hydrolysis in a microwave prior to SSF as a substrate to produce fumaric acid [80]. In the production of an anti-cancer pro-drug, camptothecine (CPT), by SSF, complex protein sources (whey concentrate powder) were added to soybean waste to enhance the productivity of Fusarium oxysporum producing a secondary metabolite [81].…”
Section: General Aspects Of Solid State Fermentationmentioning
confidence: 99%